An Evaluation of the Acceptability, Appropriateness, and Utility of a Bibliotherapy for Children of Parents With a Mental Illness - Vetri, Kelly; Piché, Geneviève; Villatte, Aude (Frontiers in Psychiatry, 2022)
Background. Children of parents with a mental illness are at higher risk for various psychiatric problems and adaptive difficulties compared to those of parents without mental health problems. Certain preventive psychoeducational interventions target these children to promote their well-being and resilience and prevent the emergence of adaptive difficulties. However, few such interventions have been developed and evaluated specifically for elementary school-aged children of parents with a mental illness. Objectives. This study aims to evaluate an interpersonal psychotherapy-based book targeting children living with a parent with a mental illness. Methods. The study examines children, parents and psychosocial workers’ perception of the acceptability, appropriateness and utility of the book. In total, 22 participants answered online open-ended questions after reading the book. Results. The book was highly appreciated and positively perceived by the families and psychosocial workers. Results suggest that children, parents and psychosocial workers viewed it as an appropriate and useful tool for supporting children with a parent with a mental illness. The present study reveals that the bibliotherapy appears well adapted to the developmental level of school-age children. Discussion. This study presents a book that shows promise for supporting the resilience of elementary school-aged children having a parent with a mental illness. Results highlight the importance of tailoring the content and modalities of interventions to the developmental level, needs and preferences of elementary school-aged children. The relevance of a collaborative method is also discussed, thus providing knowledge regarding this type of approach for the development of interventions targeting children.